Occurrence of Ariostolochic Acids in Over-the-counter Chinese Prepared Medicines - Annie Ho, Ja-An; Kuo, Hung-Yi; Wang, Yun-Tse; Yang, Chung-Shi (Asian Journal of Chemistry, 2010)
The purpose of the present study was to investigate the levels of aristolochic acids (AA-I and AA-II) in Chinese herbal medicines and in over-the-counter Chinese prepared medicines using high-performance liquid chromatography (HPLC). Reversed-phase HPLC (C18) utilizing isocratic elution (65% methanol, 35% water, 0.5% acetic acid) and UV detection (λ=254 nm) was used to survey 11 different kinds of Chinese herbal medicines that were known to be consumed by patients prior to be hospitalized for acute renal failure. It was found that 8 out of 11 samples contained aristolochic acids (ranging from 0.2 to 20 nmol/g. These results suggested that commercially available over-the-counter Chinese herbal medicines might contain various levels of aristolochic acids.